GE_GERICHTE PM/1011/2017 vom 2. Oktober 2017 - GE Cour de justice (2017)
EXPULSION(DROIT DES ÉTRANGERS); EXPULSION(DROIT PÉNAL); RENVOI(DROIT DES ÉTRANGERS); PRONOSTIC; INTÉGRATION SOCIALE; REPORT(DÉPLACEMENT) | CP.86